The meaning of the Ceprotan tradition in bersih desa for the people of Sekar village - Laras Andita Yuningtyas; Sigit Pranawa; Yuhastina Yuhastina (Program Pascasarjana Universitas Negeri Yogyakarta, 2020)
The purifying tradition carried out by the Sekar Village community is always accompanied by a traditional ceremony called Ceprotan. This Ceprotan traditional ceremony only exists in Sekar Village. Its implementation load with folklore values that the local people believe. This study aimed to know the meaning of the Ceprotan tradition for the people of Sekar village. This research used a qualitative method with a phenomenological approach. The intake of informants was done through the purposive sampling technique. Data obtained using both secondary and polymer data. Data collection techniques used were interviews, observation, and documentation. To ensure the validity of the data, the researcher used source triangulation techniques on the data obtained. The data were then analyzed with cultural interpretation techniques or the